Features of conformal behavior in adolescence (Actual Problems of Psychology in Educational Institutions, 2019)
The article is devoted to the problem of identificationconformal behavior in youth. The author outlines the content of the concept ofconformism and conformality, features of the identification of conformism inthe social group. Specifications of the conformal type of personality arespecified. The connection of the conformality of the personality with theself-estimation of a person is shown.Socio-phyhological personality peculiarities of the youth have beendefined and investigated. It is proved that conformism is a progressive andnatural phenomenon of the period of maturation. The empirical study based onthe peculiarities of conformal behavior and self-esteem at the age of youth hasbeen run. According to the results of correlation analysis, the existence of aninverse relationship between the indicators of conformal behavior of boys andthe level of their self-esteem.
Keywords: c onformism, conformal behavior, social behavior, self-esteem, the period of youth